Psychosocial Impacts of Mobile Game on K12 Students and Trend Exploration for Future Educational Mobile Games - Li, Yuanzhe; Xu, Zezheng; Hao, Yu; Xiao, Peng; Liu, Jingyan (Frontiers in Education, 2022)
Due to the popularity and advancement of 4G/5G networks, mobile games have already currently become profitable tools for major internet platforms. These games are even refined to cover almost all age groups of the population rather than the young people. Yet in the perception of the public, mobile games have always seemed to be associated with various derogatory terms such as interfering with learning, addiction, and violence. K12 students usually have less self-control capability, and they are undoubtedly the biggest advocates of mobile games. This paper summarizes the technological development of mobile games from the aspects of hardware and software in chronological order. The psychological and social problems that mobile games have brought to K12 students are analyzed from a neutral perspective. At the end of the paper, the future development of educational games and current limitations of mobile games are also given for the explorations of future trends of game-based education. This position paper aims to provide the insight of what psychosocial impacts that the current mobile games have on the student, and it may also serve as a reference for the how the game-based education has been developing according to the mobile technology wise.